(untitled) - Clark, Kim B. (Boston, Mass., 1991)
The result of six years of research conducted at the Harvard Business School on how different manufacturing firms around the world approach the development of new products. Its principal focus is on the impact of strategy, organization, and management on this critical component of business strategy. Concentrates on case studies from the world auto industry. Drawing on extensive research on twenty companies in Europe, North America, and Japan, the authors identify the strategies, practices, and capabilities that create superior performance in lead time, engineering productivity, and total product quality. The authors make the general applications of their findings clear to other industries. Managers will see how engineering needs to become more customer oriented, how integrated problem-solving activities pay off, how lead times can be cut without damaging side effects, and how strong project leaders championing products can promote innovative results.
Keywords: Automobile industry and trade; Management